Metodologia de caracterização e modelagem de tráfego para transmissão de imagens médicas - Silva, Robert Paulo Barbosa e (2015)
Characterization and traffic modeling in medical image transmission is an important activity for corporate network management. With popularization of medical imaging a lot of information about the patients became available. This new form of digital high-definition images has been integrated into computer networks over the years, using the DICOM protocol. Recently, a large amount radiological equipament has been used for medical image generation transmission, thus causing new challenges for monitoring and management of network operations. This paper presents a methodology for modeling DICOM traffic. Traffic measurements were carried out on the network and direct collections in radiological equipment of a small hospital for analysis. Measurements on the network traffic were performed to characterize the behavior of the traffic, thereby identifying the model and composition of the network. The traffic source capture were executed over year to traffic from real medical diagnosis. The modeling of the traffic source was performed using curve fitting statistical techniques, to model the distribution of image file sizes. Compliance tests analysis showed the Dagum distribution as the best approach in these results. Thus, the traffic source model suggested by this work can be used in simulation experiments and network expansion projects.